2017
DOI: 10.1016/j.cattod.2016.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the photoelectrochemical properties of C, N, F codoped TiO 2 nanotubes of different lengths

Abstract: a b s t r a c tThe aim of this work has been the photoelectrochemical (PEC) study of nanostructured photoanodes based on TiO 2 . Highly ordered and well adhered TiO 2 nanotubes (TNTs) of different lengths (∼2-20 m) were prepared in a two-step process in ethylene glycol solutions containing fluorides, and detailed XPS analysis showed that they have become co-doped with C, N and F. PEC measurements revealed that increasing surface area is not followed by increase in the photoconversion efficiency, but rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
3
21
0
Order By: Relevance
“…Moreover, the addition of suitable content of Cu-to N-doped TiO 2 electrode effectively inhibited the growth of TiO 2 nanoparticles and improved the optical response of the photoelectrode under visible light irradiation. Chatzitakis et al [81] studied the photoelectrochemical properties of C, N, F codoped TiO 2 nanotubes. It was found that increasing surface area is not followed by increase in the photoconversion efficiency, but rather that an optimal balance between electroactive surface area and charge carrier concentration occurs.…”
Section: Co-doping and Tri-dopingmentioning
confidence: 99%
“…Moreover, the addition of suitable content of Cu-to N-doped TiO 2 electrode effectively inhibited the growth of TiO 2 nanoparticles and improved the optical response of the photoelectrode under visible light irradiation. Chatzitakis et al [81] studied the photoelectrochemical properties of C, N, F codoped TiO 2 nanotubes. It was found that increasing surface area is not followed by increase in the photoconversion efficiency, but rather that an optimal balance between electroactive surface area and charge carrier concentration occurs.…”
Section: Co-doping and Tri-dopingmentioning
confidence: 99%
“…Then, Mott‐Schottky analysis was carried out on the nanostructured SnS and SnS/ERGO in contact with the electrolyte, in order to study their semiconductor properties (flat band potential, E FB , and the apparent majority carrier density, N A ). However, as the film is formed by nanocrystals and nanostructures, a frequency dispersion of capacitance can be observed, making difficult the determination of these parameters . According with Dutoit et al .…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of doped TiO 2 nanotubes in the dopant material containing electrolytes has been studied by Chatzitakis et al They prepared C- and N-doped TiO 2 nanotubes in ethylene glycol containing small amounts of water and NH 4 F. Meanwhile, they considered the content of C and N species in the electrolyte solution as the contaminants. Consequently, the concentration of dopants was not controlled during the anodization process [ 66 ].…”
Section: Synthesis Of Porous Tio 2 Structuresmentioning
confidence: 99%